2018
DOI: 10.1016/j.anai.2018.03.028
|View full text |Cite
|
Sign up to set email alerts
|

The burden of allergic rhinitis and allergic rhinoconjunctivitis on adolescents

Abstract: Although AR and ARC are sometimes perceived as trivial conditions, this review indicates that their effect on adolescent life is negative and far-reaching. It is critical that clinicians gain a greater understanding of the unique burden of AR and ARC in adolescents to ensure they receive prompt and appropriate care and treatment to improve clinical and academic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
1
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(116 citation statements)
references
References 42 publications
3
103
1
9
Order By: Relevance
“…Allergic rhinitis (AR) is the most common immunemediated disorder as it may affect up to 40% of the paediatric population [71]. AR has clinical relevance as is frequently associated with comorbidities, including other allergies, asthma, rhinosinusitis, recurrent respiratory infections, otitis, adenoid hypertrophy (AH) and tonsillar hypertrophy (TH), as recently reported by several recent studies [72][73][74][75]. Moreover, the possible correlation between AR and AH-TH has been investigated by some studies which reported a positive association between the two disorders [76][77][78][79][80].…”
Section: Allergic Rhinitismentioning
confidence: 96%
“…Allergic rhinitis (AR) is the most common immunemediated disorder as it may affect up to 40% of the paediatric population [71]. AR has clinical relevance as is frequently associated with comorbidities, including other allergies, asthma, rhinosinusitis, recurrent respiratory infections, otitis, adenoid hypertrophy (AH) and tonsillar hypertrophy (TH), as recently reported by several recent studies [72][73][74][75]. Moreover, the possible correlation between AR and AH-TH has been investigated by some studies which reported a positive association between the two disorders [76][77][78][79][80].…”
Section: Allergic Rhinitismentioning
confidence: 96%
“…Allergic disorders affect people of all ages and can have a substantial adverse effect on an individual's QoL and their work or educational performance 3,4,36,46,[79][80][81][82] . Bilastine is effective and well tolerated in different age groups, from school-age children through to elderly adults.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of acute urticaria in children is 1-14%, and that of persistent or chronic urticaria is 0.1-1.8% 77,78 . Allergic rhinitis and urticaria both have an adverse effect on QoL in children and adolescents, causing emotional and practical problems, limitations in daily activities and sleep problems [79][80][81][82] . Of importance in this age group, allergic rhinitis and urticaria can have a negative impact on school attendance and academic achievement 81,83,84 .…”
Section: School-age Childrenmentioning
confidence: 99%
“…Allergic rhinitis (AR) is the most common immune-mediated disorder in childhood as it may affect up to 40% of children (1). AR is frequently associated with relevant comorbidities, including other allergies, rhinosinusitis, recurrent respiratory infections, otitis, adenoid hypertrophy (AH) and tonsillar hypertrophy (TH), as recently reported by several recent studies (2)(3)(4)(5)(6). Moreover, the possible correlation between AR and AH-TH has been investigated by some studies which reported a positive association between the two disorders (7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 93%